Globalization and the Gains from Variety: The Case of a Small Open Economy - Lukas Mohler (FIW - Research Centre International Economics, 2009)
Since the pioneering work of Krugman (1980) economists try to quantify the welfare gains from an increase in traded variety. The seminal work of Feenstra (1994) and its application to the U.S. of Broda and Weinstein (2006) allowed this quantification for the first time using highly disaggregated trade data. In this paper it is argued that size and openness of a country are important factors in determining these welfare gains. The gains from traded variety of a small open economy are calculated and compared to those of the U.S.; the differences between the countries are then analysed carefully. To achieve this, the methodology of Feenstra (1994) is extended. While the Armington definition of a variety forces the researcher to assume no growth at the extensive margin, in this paper the Feenstra ratios are reinterpreted in a way that allows for full growth at the extensive margin. The resulting two polar cases will influence the country comparison with respect to the gains from variety: Depending on how much growth at the extensive margin a researcher is willing to assume, the relative gains from variety of a small open economy compared to a larger economy like the U.S. are changed. It is also argued that this result may hold generally for other small and large OECD economies.
Keywords: F12; F14; 330; Welfare Gains from Trade; Trade in Variety; Small Open Economy